Measurement of Berry's phase using an atom interferometer - Webb, C; Godun, R; Summy, G; Oberthaler, M; Featonby, P; Foot, C; Burnett, K (1999)
We report on the demonstration of Berry's phase in an atomic state interacting with a laser field. We draw an analogy between this system and that of a spin interacting with a directionally varying magnetic field. This allows us to identify an effective magnetic quantum number for the atom-light system that governs the maximum Berry phase the atomic state can acquire. We realize two systems that have different effective magnetic quantum numbers, and use a recently developed atom interferometer to make measurements of Berry's phase. ©1999 The American Physical Society.